2019
DOI: 10.1038/s41561-019-0377-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesosiderite formation on asteroid 4 Vesta by a hit-and-run collision

Abstract: Collision and disruption processes of proto-planetary bodies in the early solar system are key to understanding the genesis of diverse types of main-belt asteroids. Mesosiderites are stony-iron meteorites that formed by mixing of howardite-eucrite-diogenite-like crust and molten core materials and provide unique insights into the catastrophic break-up of differentiated asteroids. However, the enigmatic formation process and the poorly constrained timing of metal-silicate mixing complicate the assignment to pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 64 publications
4
60
0
Order By: Relevance
“…9; Yamaguchi et al 2002;Schwartz and McCallum 2005). However, Haba et al (2019) reported Pb-Pb ages of 4525.4 AE 0.9 Ma for mesosiderite zircons, which is consistent with the 4523 AE 2 Ma metamorphic age of NWA 6594 with high precision. They suggest that the 4525.4 AE 0.9 Ma event was induced by a giant impact that led to metal-silicate mixing and formation of mesosiderites, which may also be related to a large-scale reheating event on Vesta.…”
Section: Discussionsupporting
confidence: 60%
“…9; Yamaguchi et al 2002;Schwartz and McCallum 2005). However, Haba et al (2019) reported Pb-Pb ages of 4525.4 AE 0.9 Ma for mesosiderite zircons, which is consistent with the 4523 AE 2 Ma metamorphic age of NWA 6594 with high precision. They suggest that the 4525.4 AE 0.9 Ma event was induced by a giant impact that led to metal-silicate mixing and formation of mesosiderites, which may also be related to a large-scale reheating event on Vesta.…”
Section: Discussionsupporting
confidence: 60%
“…The initial 142 Nd abundance for Vesta was estimated from internal mineral isochrons of basaltic and cumulative eucrites (Boyet et al 2010 and references therein). These meteorites have a similar isotopic evolution as angrites and in particular mesosiderites, which is also reflected in the similarity of U-Pb ages of zircons separated from these meteorites (Haba et al 2019). Their 146 Sm-142 Nd evolution, when compared with the crystallization ages, is most consistent with a source that had a composition similar to ordinary chondrites (Gannoun et al 2011).…”
Section: Constraints On Planetary Building Blocks From Radiogenic Isomentioning
confidence: 59%
“…The metal component shows some similarities to IIIAB iron meteorites (Hassanzadeh, et al 1990), whereas the silicate fraction has been compared with basaltic or pyroxenitic Howardite-Eucrite-Diogenite (HED) meteorites (e.g., Clayton and Mayeda 1996;Greenwood et al 2015). A common origin of the silicate fraction of mesosiderites and the HED from the asteroid 4-Vesta has been disproved (Rubin and Mittlefehldt 1993) and recently proposed again (Haba et al 2019). The simultaneous presence of silicate and metal is interpreted as a mixture of basaltic material from the crust and metal from the core, originating either by collision of two differentiated parent bodies (Wasson and Rubin 1985) or from mixing within the same parent body (Mittlefehldt et al 1998;Scott et al 2001).…”
Section: Introductionmentioning
confidence: 99%